Perancangan Game Edukasi Alat Musik Interaktif Piano, Saron dan Drum Berbasis Web - Ryan Aji Wijaya; M. Abu Jihad Plaza R; Yulina (Sienna, 2025)
In an era of rapidly evolving technology, the advancement of online applications has become a powerful method for enhancing children's imagination and abilities across various fields, including music. This research focuses on the design and implementation of an electronic smart music game for three instruments: piano, saron, and drums, based on a web platform. The primary objective of this application is to attract children's interest in learning instruments through engaging and easily accessible online media. The development technique employed is the Software Development Life Cycle (SDLC) using the Waterfall model, which integrates the phases of requirements analysis, planning, implementation, and testing. Use case diagrams, activity diagrams, and sequence diagrams were utilized during the planning stage to define the system framework using Unified Modeling Language (UML). The implementation was completed using Visual Studio Code and programming languages including HTML, CSS, and JavaScript. The results of this design indicate that this music game application can effectively and enjoyably assist children in learning musical instruments. Furthermore, the application fosters children's interest in music while supporting their cognitive and emotional development. With its simple and accessible features, this application is expected to become a significant asset for music and social education in Indonesia, while helping to build awareness and enthusiasm for both traditional and modern music.